The Effect of Alopurinol on Blood Urea Nitrogen and Creatinine Serum Levels in Patients with Chronic Kidney Disease - Miftakhul Huda; Pulong Wijang Pralampita; Dini Agustina; Cholis Abrori; Septa Surya Wahyudi (Faculty of Medicine, University of Jember, 2021)
Chronic kidney disease (CKD) is a structural and function disorder of renal for > 3 months with implications for individual health. CKD has become a health problem throughout the world and its implementation provides a considerable economic burden on the health system. The decreasing value of GFR (glomerular filtration rate) in CKD can cause uric acid retention so that serum uric acid levels increase (hyperuricemia). Hyperuricemia can occur due to an increase in urinary metabolism (overproduction), a decrease in uric acid expenditure (underexcretion), or a combination of both. The group of antihyperuricemic drugs that have good effectiveness and long-term safety is xanthine oxidase inhibitors. The commonly used xanthine oxidase inhibitor drug is allopurinol. The purpose of this study was to determine whether there was an effect of allopurinol on kidney function in CKD patients. The results of this study are expected to provide input in the treatment of hyperuricemia in CKD patients and reduce the progression of CKD. This study used a retrospective observational analytic design with a cross-sectional approach. The study population was CKD patients from January 2018 to January 2019 at Bina Sehat Hospital Jember. The sampling technique uses purposive sampling. This study uses secondary data obtained from medical records of CKD patients at Bina Sehat Hospital Jember. Secondary data obtained in the form of identity data and the results of laboratory tests of patients. The medical record data that has been obtained is distributed and analyzed using a paired T-test to compare the mean or mean differences of the two groups in pairs. The bivariate test results for blood urea nitrogen and serum creatinine levels in CKD patients were obtained p <0.001. Based on these results there is a significant relationship between blood urea nitrogen and serum creatinine levels before and after consuming allopurinol. The conclusion was that allopurinol was shown to be able to provide an effect on the kidney function of CKD patients based on blood urea nitrogen and serum creatinine levels. Keywords: Chronic kidney disease, hyperuricemia, allopurinol